Production of silicon particles with reduced surface metal content
By using a combined solution of pre-etch bath and main etch bath during the etching and cleaning of silicon fragments, the problem of difficulty in removing surface metal impurities when pulverizing polysilicon is solved, and efficient cleaning of silicon fragments is achieved and the cleaning requirements of semiconductor applications is met.
Patent Information
- Application Number
- CN202280099641.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-22
- Publication Date
- 2025-04-08
AI Technical Summary
The prior art is difficult to effectively remove surface metal impurities, especially tungsten, when pulverizing polysilicon, which results in the cleanliness of silicon fragments not sufficient to meet the requirements of semiconductor applications.
The etching cleaning was performed using a combined solution of hydrofluoric acid (HF) and nitric acid (HNO3) by contacting the pulverized silicon fragments with a pre-etching bath and a main etching bath. The pre-etch bath contains 6.6% to 12% HF and 40% to 65% HNO3, and the main etch bath contains 5.3% to 6.5% HF and 40% to 65% HNO3.
It significantly improves the removal efficiency of tungsten, reduces the total surface metal content (SFM), and reaches less than 13pptw, meeting the cleaning requirements of semiconductor applications, while reducing the different chemicals used.
Smart Images

Figure BDA0005290352550000091 
Figure BDA0005290352550000141 
Figure BDA0005290352550000142
Abstract
Description
Technical Field
[0001] The invention relates to a method for producing silicon fragments (silicon chips, silicon fragments, chunks) with reduced surface metal content, wherein a silicon ingot or block is comminuted and the resulting silicon fragments are contacted with a pre-etching bath and at least one main etching bath. Background Art
[0002] Polysilicon is usually produced by the Siemens process (chemical vapor deposition process). Polysilicon is the starting material in the production of single-crystal silicon, which is produced, for example, by the Czochralski process. In addition, polysilicon is required for the production of multicrystalline silicon, for example by a block casting process. For both methods, the polysilicon obtained in the form of an ingot according to the Siemens process must be crushed into fragments.
[0003] In semiconductor applications, reducing surface contamination is a priority and is crucial so as not to adversely affect minority carrier lifetime (recombination and generation lifetime) and also to avoid micron-scale metal precipitation. For chip applications, for example, the total content of metal impurities can be only in the pptw range.
[0004] The process of comminuting polysilicon is fundamentally a source of contamination, especially metals. Comminuting is usually carried out using rollers or jaw crushers. Although the use of particularly wear-resistant materials (e.g. tungsten carbide, silicon nitride, silicon carbide and polycrystalline diamond) can reduce metal contamination, a certain level of wear during the comminuting process cannot be completely prevented. Therefore, at least for the further uses mentioned above, cleaning of the comminuted polysilicon is indispensable.
[0005] Cleaning is mainly performed using a wet chemical etching process, in which the crushed polysilicon is successively transferred into different acid and / or alkaline baths. The purpose of cleaning is to remove surface impurities such as metals and dopants, as well as greases and oils. In particular, the removal of elemental tungsten presents a challenge, due to the common use of WC / Co-based crushing tools, resulting in uncleaned material after crushing that can have a tungsten content of 400-1000 pptw.
[0006] US 6,309,467 B1 discloses a material having a thickness less than 6.66*10 -11 g / cm 2 Silicon fragments with a low Fe and Cr content are obtained by a multi-stage wet chemical process, in which the material passes through different corrosive HF / HNO3 and purified (HF, HCl and H2O2) baths. The material is guided through separate troughs by a lifting and lowering motion. However, tungsten cannot be effectively removed from the Si surface.
[0007] US 2010 / 0132746 A1 describes a cleaning device with multiple etching baths. Here, the HNO3 content increases continuously from the first etching bath to the last etching bath. The HF content in all baths is only 0.1%-0.5%. The cleaned material still has a surface metal content of less than 0.01 ng / mL, which may be due to the low HF content.
[0008] US 2021 / 0114884 A1 discloses an etching process, particularly for removing tungsten from silicon surfaces. It will pass through three etching baths, the middle bath contains an alkaline aqueous solution with H2O2 and tetramethylammonium hydroxide (TMAH), and the other two baths contain HF / HNO3 solutions. The metal content of the surface after treatment is 15pptw or less, and the tungsten content is 0.9pptw or less.
[0009] In addition to the HF / HNO3-based step, the cleaning process according to US 2014 / 0037959 A1 also includes an alkaline etching step. Compared with US 2021 / 0114884 A1, this step is carried out by introduction. The disadvantage of the alkaline cleaning step is that the reaction time is usually slow, which hinders the particularly fast operation of the cleaning system. In addition, organic bases such as TMAH can lead to an increase in the carbon content on the surface. In addition, the treatment of other corrosive components leads to additional equipment costs.
[0010] US 2013 / 0189176 A1 describes a two-stage cleaning process for polysilicon by an acid wash mixture (HF / HCl / H2O2) followed by an etching bath (HF / HNO3). The cleaned material has a surface metal content of 10 pptw to 100 pptw. The tungsten content is reported to be 0.1-10 pptw. However, comminution of the polysilicon does not occur here using a crushing tool containing tungsten carbide. The cleaning conditions described are not sufficient to effectively remove tungsten impurities resulting from the use of a tungsten-containing crushing tool. Summary of the invention
[0011] Starting from the stated disadvantages, it is an object of the present invention to provide an efficient method for removing surface metals, in which as few different chemicals as possible are used. The focus here is on the efficient removal of tungsten.
[0012] This object is achieved by a method for producing silicon fragments, preferably polycrystalline silicon fragments, having a reduced surface metal content, comprising the following steps:
[0013] a) crushing silicon ingots or silicon blocks into silicon fragments,
[0014] b) contacting the silicon fragments with at least one pre-etching bath comprising 6.6% to 12% by weight of hydrofluoric acid (HF) and 40% to 65% by weight of nitric acid (HNO3),
[0015] c) contacting the silicon fragments with at least one main etching bath comprising 5.3 to 6.5% by weight HF and 40 to 65% by weight HNO3.
[0016] With regard to the comminution of silicon and the apparatus for carrying out the method, reference may be made to US 2006 / 008970 A1 and US 2014 / 0037959 A1.
[0017] The contacting of the silicon fragments with the respective etching baths is preferably carried out by a combination of a lowering movement and a lifting movement, wherein the fragments are in a process pan and the etching solutions are each in a tank. In other words, the contacting can thus comprise an immersion process. The composition of the etching baths can be continuously monitored by titration.
[0018] Surprisingly, it has been shown that processing the silicon fragments in at least one upstream etching bath (having an increased HF concentration compared to the main etching bath) can achieve significantly better tungsten removal. It is particularly advantageous that this improvement does not come at the expense of poorer removal of other metals from the total surface metal content (SFM) considered. In addition to tungsten, the metals considered are as follows: Fe, Cr, Ni, Al, Ca, Ag, Zn, As, Co, Cu, Na, K, Ti, Mg, Mo, Mn, Sn, Ba, Bi, Cd, Li, Pb, Sb, Sr, Tl, U, V, Y, Zr. The total SFM is the sum of the metals expressed in pptw and is referred to as SFM hereinafter. The total SFM can be reduced to less than 13 pptw, preferably less than 12 pptw, more preferably less than 11 pptw by the method of the present invention with a total 99% quantile.
[0019] Furthermore, the cleaning method of the invention can advantageously be limited to treatment with only one etching solution (HNO3 / HF).
[0020] Preferably, the silicon fragments are contacted with only one pre-etch bath.
[0021] Preferably, the pre-etch bath comprises 6.6 to 12%, more preferably 7 to 10% by weight HF.
[0022] The contact time of the silicon fragments in the pre-etching bath is preferably 1 to 30 s, more preferably 2 to 25 s, and more particularly 4 to 20 s. The etching reduction caused thereby is therefore typically only about 1 μm to 3 μm.
[0023] The temperature of the pre-etching bath is preferably 1 to 60° C., more preferably 5 to 50° C., more particularly 8 to 40° C. The temperature in the etching circuit can be detected via a temperature sensor in the medium circuit (measuring principle: PT100) and controlled to a set point value. Further monitoring can be carried out directly in the etching bath by an additional temperature sensor (measuring principle: PT100).
[0024] According to a particularly preferred embodiment, the temperature of the pre-etching bath is set according to the fragment size category of the silicon fragments to be cleaned. The temperature for fragment size 2 (CS2) is preferably 1 to 10°C; for CS3, preferably 8 to 60°C; and for CS4, preferably 1 to 15°C.
[0025] Crumble size classes 0 to 4 (CS0 to CS4) are defined essentially using the grain size of the crumbs, where the grain size is defined as the longest distance between two points on the surface of the silicon crumbs. Crumble size classes include fractions having the following particle size ranges.
[0026] CS0: 1 to 6 mm
[0027] CS1: 3 to 15 mm
[0028] CS2: 4 to 45mm
[0029] CS3: 10 to 65mm
[0030] CS4: 20 to 150mm
[0031] The pieces of CS4 usually have the smallest specific surface area and the lowest tungsten contamination from the crushing process. The reason for this is only one contact with the crushing tool (e.g., double roll crusher). Therefore, the contamination level is quite low and removal by cleaning at reduced etching temperatures is possible.
[0032] The fragments of CS2 usually have the highest specific surface area and thus increased tungsten contamination from the fragmentation process. The large surface area leads to high local temperatures on the fragments during the etching process. For reliable reaction control, the etching bath temperature is therefore usually kept low.
[0033] During etching, fragments of CS3 generally exhibit the most unfavorable relationship between specific surface area, tungsten contamination and local temperature at the fragment surface. In order to obtain more effective removal by cleaning, the etching bath temperature is therefore generally increased.
[0034] Silicon fragments can be sorted by a sieve, wherein the edge length of the square mesh corresponds to the upper limit of CS. For example, US2016 / 0214141 A1 describes a sorting process using a vibrating sieve.
[0035] Preferably, the CS comprises at least 90% by weight of silicon fragments within the corresponding size range.
[0036] The (silicon) fragment bed with a preferably narrow fragment size distribution is usually measured and analyzed using a particle size instrument. Preferably, for CS3 and CS4, the weight is first determined by gravimetry and the maximum fragment length and width of the individual fragments are then determined optically by image processing. Below a fragment size CS3, the maximum fragment length and width are determined by the principle of light / laser scattering. From the calculated average length to weight ratio or width to length ratio (aspect ratio), conclusions can be drawn about the cubicity or roundness of the fragment bed. For CS4, the aspect ratio of weight to maximum length is preferably in the value range of 0.2 mm / g to 1.0 mm / g; for CS3, typical values range from 1.2 mm / g to 5.0 mm / g. For CS2 and less than 45 mm, the width to length ratio is formed when measuring using light / laser scattering. The aspect ratio here represents the greater cubic volume fraction of the bed, which falls within the range of the width to length ratio below 0.5. The value is preferably from 0.4 to 0.8.
[0037] The morphology of the fragments treated by the method of the invention is essentially irrelevant to its implementation / effectiveness.
[0038] In method step c), the temperature of the at least one main etching bath is preferably 1 to 15° C., more preferably 2 to 12° C., more particularly 4 to 10° C. If two or more main etching baths are used, they preferably do not differ or differ only insignificantly (fluctuations within ±1° C.) in their temperature.
[0039] The silicon fragments are particularly preferably contacted with only one main etching bath. Preferably, the main etching bath here contains 53 to 65% by weight of HNO3.
[0040] The residence time (immersion time) of the silicon fragments in only one main etching tank is preferably 35 to 180 s, more preferably 60 to 150 s.
[0041] Furthermore, it may be preferred that the silicon fragments are contacted with a first and a second main etching bath in step c), in which case the second main etching bath has a higher HNO3 content. Preferably, the first main etching bath contains 40 wt% to 65 wt%, more preferably 45 wt% to 60 wt% HNO3, and the second main etching bath contains 53 wt% to 65 wt% HNO3.
[0042] When two main etching tanks are used, the residence time of the silicon fragments in the first main etching tank is preferably 35 to 180 s, more preferably 60 to 150 s, and the residence time in the second main etching tank is preferably 35 to 180 s, more preferably 60 to 150 s.
[0043] If more than two main etching baths are used, the HNO 3 content preferably increases from the first main etching bath to the last main etching bath.
[0044] The HF content is preferably kept constant.
[0045] The acid mixture from the main etching bath can be supplied to the pre-etching bath via a cascade through the tank overflow. This cascade is conducive to the economical use of acid. By specific metering, the required concentration of each etching tank is established and maintained.
[0046] The process preferably comprises, after step c), a further step d), in which the silicon fragments are contacted with a hydrophilic bath comprising an ozone-water mixture having 5 to 30 ppm, preferably 7 to 15 ppm, of ozone.
[0047] Furthermore, it may be preferred that the silicon fragments are contacted with an ultrapure water bath after each of steps a), b), c) and optionally d). The contact with the ultrapure water bath may also be carried out after only one or two or more of steps a) to d).
[0048] Preferably, after the comminution in step a) and before the transfer to the pre-etching bath, a so-called entry washing of the silicon fragments is carried out in an ultrapure water bath.
[0049] Furthermore, it is preferred that after step d) the silicon fragments are contacted with an ultrapure water bath, which preferably has a temperature of 50 to 95°C, more preferably 60 to 90°C.
[0050] The preferred residence time of the silicon fragments in the ultrapure water bath, regardless of which process step they follow, is from 15 to 180 s, more preferably from 30 to 150 s.
[0051] Preferably, no ultrapure water bath is provided between the pre-etching bath and the at least one main etching bath.
[0052] In some cases, the silicon fragments may additionally be contacted with an acid wash bath. The bath preferably comprises 10 to 13% by weight of HCl, 4 to 6.5% by weight of HF and 1.4 to 2% by weight of hydrogen peroxide. The acid wash bath may in particular be provided between steps a) and b).
[0053] The method may include a drying step, wherein the silicon fragments are dried by convection drying and / or vacuum drying.
[0054] The drying step may be after step c), step d), or after an ultrapure water bath following one of said steps.
[0055] Preferably, an ultrapure water bath (hot water wash) having a temperature of 80° C. to 95° C. is provided before the drying step.
[0056] Preferably, the drying step comprises convection drying at 60° C. to 100° C., preferably 70° C. to 90° C., followed by vacuum drying at 2 kPa to 8 kPa (temperature range 18° C. to 25° C.), preferably 3 kPa to 5 kPa. The typical residence time of the silicon fragments in convection drying is 800 to 3000 s (e.g. 1250 s at 80° C.). In vacuum drying, the time is typically 50 to 400 s (e.g. 100 s at room temperature and 3.5 kPa).
[0057] A further aspect of the invention relates to silicon fragments, more particularly silicon fragments produced according to the method, having a SFM at the 99% quantile of less than 20 pptw, preferably less than 15 pptw, more preferably less than 11 pptw, more particularly less than 8 pptw. When determining the surface metal content, the following metals are considered: Fe, Cr, Ni, Al, Ca, Ag, W, Zn, As, Co, Cu, Na, K, Ti, Mg, Mo, Mn, Sn, Ba, Bi, Cd, Li, Pb, Sb, Sr, Tl, U, V, W, Y, Zr.
[0058] The tungsten content at the 99% quantile is preferably ≤1 pptw, more preferably ≤0.6 pptw, and most particularly ≤0.3 pptw.
[0059] The content of Fe, Cr, Ni and W is preferably ≤5 pptw, more preferably ≤4 pptw, and more particularly ≤3 pptw.
[0060] The surface metal content can be determined according to SEMI MF1724. A mixture of HF (40% by weight) / HNO3 (65% by weight) in a ratio of 1 / 4 v / v (e.g., 250 mL of HF and 750 mL of HNO3) is used to separate the surface layer (overetching) of the fragments, which are then pyrolyzed until dry. The residue is redissolved in a beaker with HF (40% by weight) / HNO3 (65% by weight) and H2O (e.g., 1450 μL per sample) in a ratio of 1 / 1 v / v (e.g., 25 μL each) and then analyzed by inductively coupled plasma mass spectrometry (ICP-MS; Agilent 8900-ICP QQQ). The initial mass of the fragments is weighed according to the fragment size and adapted to the specific surface area. It is 15 g to 180 g.
[0061] The detection limit (method detection limit; MDL) is calculated using the blank scatter. As specified in the BLMP guidelines for method validation (German Federation / State measurement procedures; ISSN 0722-186X), the direct method (blank value method) according to DIN 32486 is calculated as follows for this purpose:
[0062]
[0063] The detection limits for the various elements are, on an annual average, 0.06 pptw for W; 1.03 pptw for Fe; 0.27 pptw for Cr; and 0.51 pptw for Ni. The detection limits for the other elements from the series Al, Ca, Ag, Zn, As, Co, Cu, Na, K, Ti, Mg, Mo, Mn, Sn, Ba, Bi, Cd, Li, Pb, Sb, Sr, Tl, U, V, W, Y and Zr are, on an annual average, 0.01 pptw to 2.01 pptw. Here the elements Mo, Li, V, Mn, Zr, Pb, Sr, Y, Bi, Cd, Tl and U do not exceed 0.03 pptw. Co, Ba and As do not exceed 0.07 pptw, and Na, Mg, Al, K, Ti, Cu, Zn, Ag, Sn and Sb do not exceed 0.78 pptw. Ca as an environmental element had the highest detection limit of 2.01 pptw. This resulted in an average detection limit of 0.3 pptw for all 30 elements. DETAILED DESCRIPTION
[0064] Example
[0065] General information:
[0066] Multicrystalline polysilicon is crushed with a crushing tool (WC) containing WC / Co. Tungsten contamination presents a challenge. Due to the so-called keep-it-clean treatment of the obtained polycrystalline silicon fragments between crushing and packaging, cross contamination through contact with foreign surfaces (e.g. gloves, metal surfaces, etc.) is prevented (keep-it-clean concept). The cleaning of the fragments in the etching system in a specific 5 kg processing tray enables the fragments to be packaged directly and contactlessly in product bags in a clean room (no-touch principle). Keep-it-clean therefore describes the concept of ensuring that the crushed Si fragments come into contact with as few potentially contaminated surfaces as possible until the packaging step. In this way, etching ablation can be reduced to a minimum. Depending on the fragment size and morphological properties, the Si fragments have a diameter of 1200 to 3500 cm 2 Depending on the fragment size, a suitable measurement method is dynamic image analysis using, for example, the data from Retsch or Haver Camsizer (Geometric Product Specifications (GPS) - Dimensional measuring equipment; Altimeters - Design and metrological characteristics (ISO 13225:2012); German version EN ISO13225:2012).
[0067] The morphological properties of the fragments can be detected by a camera system and represented by a morphological index as disclosed in WO 2021 / 121558 A1.
[0068] 5 kg of silicon fragments are used in each embodiment. The fragments are derived from the same batch of the Siemens process. The fragments are located in a process carrier for 5 kg of product quantity, preferably made of plastic (e.g., PVDF), and are immersed in various cleaning baths in turn. The etching bath is made of polyvinylidene fluoride. The typical filling amount of the bath is 300-700 L. The cleaning process is automatically carried out in the cleaning pipeline, where the immersion is caused by the descending and lifting movement. The acid composition of the bath is continuously monitored by pH titration. In each case, after the last processing step, the analysis of the cleaned product is carried out by ICP-MS (method description see SEMI MF1724) with the help of a sample amount depending on the size of the fragments. For CS3, the sample amount is about 80 g.
[0069] Example 1
[0070] 5 kg of CS3 silicon fragments were passed through the following process steps:
[0071] - Pre-etching bath: 45% by weight HNO3 and 7.0% by weight HF in ultrapure water; bath temperature: 50°C; residence time: 4 s (usually the residence time can be achieved by one or more immersions).
[0072] - Main etching bath: 50wt% HNO3 and 5.8wt% HF in ultrapure water; bath temperature: 8°C; dwell time: 130s
[0073] -Ultrapure water bath: bath temperature: 18°C; residence time: 120s;
[0074] -Convection drying: temperature: 80°C; residence time: 1250s
[0075] -Vacuum drying: pressure: 3.5kPa; residence time: 100s
[0076] Example 2
[0077] 5 kg of CS2 silicon chips were passed through the process steps presented in Example 1. Compared to Example 1, the temperature of the pre-etching bath was 4° C. and the residence time in the main etching tank (temperature 5° C.) was only 100 s.
[0078] Example 3
[0079] 5 kg of CS4 silicon chips were passed through the process steps presented in Example 1. Compared to Example 1, the temperature of the pre-etching bath was 4° C. and the residence time in the main etching tank (temperature 8° C.) was only 100 s.
[0080] Example 4
[0081] 5 kg of CS2 silicon fragments with non-dense morphology (fragments with growth structures such as dendrites / corals, cracks and holes) were passed through the process steps proposed in Example 1. Compared to Example 1, the temperature of the pre-etching bath was 4°C and the residence time in the main etching tank was only 100 s at a temperature of 5°C.
[0082] Comparative Example 1
[0083] 5 kg of CS3 silicon fragments were passed through the following process steps:
[0084] - Main etching bath: 50wt% HNO3 and 5.8wt% HF in ultrapure water; bath temperature: 8°C; dwell time: 130s
[0085] -Ultrapure water bath: main etching tank and then rinse tank, bath temperature: 18°C; residence time: 120s
[0086] -Convection drying: temperature: 80°C; residence time: 1250s
[0087] -Vacuum drying: pressure: 3.5kPa; residence time: 100s
[0088] Comparative Example 2
[0089] 5 kg of CS2 silicon fragments were passed through the following process steps:
[0090] - Main etching bath: 5.8% by weight HF; 50% by weight HNO3; bath temperature: 5°C; dwell time: 100s
[0091] -Ultrapure water bath: bath temperature: 18°C; residence time: 120s;
[0092] -Convection drying: temperature: 80°C, residence time: 1250s
[0093] -Vacuum drying: pressure: 3.5kPa; residence time: 100s
[0094] Comparative Example 3
[0095] 5 kg of CS4 silicon fragments were passed through the process steps of Comparative Example 2, except that the temperature of the main etching bath was 8°C.
[0096] Comparative Example 4
[0097] 5 kg of CS2 silicon fragments having a non-densified morphology were passed through the process steps described in Comparative Example 2.
[0098] Comparative Example 5
[0099] 5 kg of CS3 silicon fragments were passed through the following process steps:
[0100] - Pickling bath: HCl content: 12% by weight; HF content: 5% by weight, H2O2 content: 2% by weight; bath temperature: 18°C; residence time: 415s
[0101] -Ultrapure water bath: bath temperature: 18°C; residence time: 80s
[0102] - Main etching bath: HF content 5.8% by weight; HNO3 content 50% by weight; bath temperature: 8°C; residence time: 130s
[0103] -Ultrapure water bath: bath temperature: 18°C; residence time: 150s
[0104] -Convection drying: temperature: 80°C; residence time: 1250s
[0105] -Vacuum drying: pressure: 3.5kPa; residence time: 100s
[0106] Table 1 summarizes Examples 1 to 4 of the invention.
[0107]
[0108] *Fe, Cr, Ni, Al, Ca, Ag, W, Zn, As, Co, Cu, Na, K, Ti, Mg, Mo, Mn, Sn, Ba, Bi, Cd, Li, Pb, Sb, Sr, Tl, U, V, Y, Zr
[0109] Table 1
[0110] Table 2 summarizes Comparative Examples 1 to 5.
[0111]
[0112] *Fe, Cr, Ni, Al, Ca, Ag, W, Zn, As, Co, Cu, Na, K, Ti, Mg, Mo, Mn, Sn, Ba, Bi, Cd, Li, Pb, Sb, Sr, Tl, U, V, Y, Zr
[0113] Table 2.
Claims
1. A method for producing silicon fragments having a reduced surface metal content, comprising the steps of: a) crushing silicon ingots or silicon blocks into silicon fragments, b) contacting the silicon fragments with at least one pre-etching bath comprising 6.6% to 12% by weight of hydrofluoric acid and 40% to 65% by weight of nitric acid, c) contacting the silicon fragments with at least one main etching bath comprising 5.3% to 6.5% by weight of hydrofluoric acid and 40% to 65% by weight of nitric acid.
2. The method according to claim 1, characterized in that The pre-etch bath contains 6.6 to 12%, preferably 7 to 10% by weight of hydrofluoric acid.
3. The method according to claim 1 or 2, characterized in that: The contact time in the pre-etching bath is 1 s to 30 s, preferably 2 s to 25 s, more preferably 4 s to 20 s.
4. The method according to any one of the preceding claims, characterized in that The pre-etching bath has a temperature of 1°C to 60°C, preferably 5°C to 50°C, more preferably 8°C to 40°C.
5. The method according to any one of the preceding claims, characterized in that The temperature of the pre-etching bath is set according to the fragment size of the silicon fragments, wherein the temperature is: For piece size 2, 1°C to 10°C, For piece size 3, 8°C to 60°C, and For piece size 4, 5°C to 15°C.
6. The method according to any one of the preceding claims, characterized in that The at least one main etching bath has a temperature of 1 to 15°C, preferably 2 to 12°C, more preferably 4 to 10°C.
7. The method according to any one of the preceding claims, characterized in that In step c), the silicon fragments are contacted with a main etching bath, which preferably contains 53 to 65% by weight of nitric acid.
8. The method according to any one of the preceding claims, characterized in that In step c), the silicon fragments are brought into contact with a first main etching bath and a second main etching bath, the second main etching bath having a higher nitric acid content.
9. The method according to claim 8, characterized in that The first main etching bath contains 40% to 65% by weight nitric acid, and the second main etching bath contains 53% to 65% by weight nitric acid.
10. The method according to any one of the preceding claims, comprising, after step c), a further step d) of contacting the silicon fragments with a hydrophilic bath comprising an ozone-water mixture having 5 ppm to 30 ppm, preferably 7 ppm to 15 ppm, of ozone.
11. The method according to any one of the preceding claims, characterized in that After each or one of steps a) to c) and / or after step d), the silicon fragments are brought into contact with an ultrapure water bath.
12. The method according to claim 10, characterized in that After step d) the silicon fragments are brought into contact with an ultrapure water bath having a temperature of 50 to 95°C, preferably 60 to 90°C.
13. The method according to any one of the preceding claims, comprising a drying step, wherein the silicon fragments are dried by convection drying and / or vacuum drying.
14. The method according to claim 13, characterized in that The drying step comprises convection drying at 60 to 100°C, preferably 70 to 90°C, followed by vacuum drying at 2 to 8 kPa, preferably 3 to 5 kPa.
15. Silicon fragments, more particularly produced by the process according to at least one of claims 1 to 14, having a surface metal content of <13 pptw, preferably <12 pptw, more preferably <11 pptw, the metals under consideration being the following: Fe, Cr, Ni, Al, Ca, Ag, Zn, As, Co, Cu, Na, K, Ti, Mg, Mo, Mn, Sn, Ba, Bi, Cd, Li, Pb, Sb, Sr, Tl, U, V, W, Y, Zr.
16. The silicon fragments according to claim 15, characterized in that: Its tungsten content is ≤1 pptw, preferably ≤0.6 pptw.
17. The silicon fragments according to claim 15 or 16, characterized in that: The content of Fe, Cr, Ni and W therein is ≤5 pptw, preferably ≤4 pptw, more particularly ≤3 pptw.
Citation Information
Patent Citations
Optimized plating process for multilayer printed circuit boards having edge connectors
US20060008970A1
Apparatus and method for washing polycrystalline silicon
US20100132746A1
Low-dopant polycrystalline silicon chunk
US20130189176A1
Polycrystalline silicon chunks and method for producing them
US20140037959A1
Classifying polysilicon
US20160214141A1